Effect of Banana Inflorescence (Musa Paradisiaca L.) on Breast Milk Production - Sri Wulan; Desri Meriahta Br Girsang (JURNAL KEBIDANAN, 2020)
The World Health Organization (WHO) recommends that babies get exclusive breastfeeding during the first 6 months, but many breastfeeding mothers are unable to give their milk because of lack of milk production. Based on the profile of the Republic of Indonesia Ministry of Health, 2017 the achievement of babies receiving exclusive breastfeeding in the North Sumatra region is still relatively low, only reaching 45.74%, the figure is far below compared to other provinces such as West Nusa Tenggara reaching 87.35%, West Sumatra 68.32 %, South Sumatra 60.36%, DKI Jakarta 67.40% and Riau province 57.65%. The purpose of this study was to determine the effect of banana inflorescence on milk production. This research used  the Eksperimen method with Pretest-Posttest With Control Group design, with the technique of taking Simple Random sampling with a sample size of 20 people, 10 experimental groups and 10 control groups. Data collection began in May-June 2020 using observation sheets and measuring cups (cc). This research used the univariate analysis with Paired T-Test and Bivariate Analysis with Independent T Test, with a significance level of 95%. The results showed an in the Eksperimen group who were given a 459 cc banana infloresence decoction and an average value in the Control group 310 cc which meant there were differences in milk production around 149 cc and p. 0.01 (0.05). Conclusion  banana inflorescence influence to  breast milk production in nursing mothers 0-6 months old.